Test of Several Concentrations of Cellulolytic Bacteria and Size of Shredded Material on the Maturity Speed of Rice Straw Compost (Oryza sativa L.) - Dini, Isna Rahma; ‎ , Hapsoh; ‎ , Wawan; ‎ , Sukendi; Wiranda, Arif (KnE Social Sciences, 2024)
This study aims to obtain the concentration of cellulolytic bacteria and the size of the chopped material on the speed of maturity of rice straw compost (Oryza sativa L.). The research was conducted at the Soil Science Laboratory, Faculty of Agriculture, Riau University from April to August 2022. This research was conducted experimentally using a non-factorial completely randomized design (CRD) with nine treatment combinations in this study. K1P1: without bacteria rice straw was not chopped, KIP2: without bacteria rice straw was coarsely chopped, KIP3: without bacteria rice straw was finely chopped. K2P1: concentration of cellulolytic bacteria 40% + rice straw was not chopped. K2P2: bacteria with a concentration of 40% + rice straw was coarsely chopped. K2P3: bacteria with 40% concentration + finely chopped straw. K3P1: bacteria with 50% concentration + unshredded rice straw, K3P2: bacteria with 50% concentration + coarsely chopped rice straw. K3P3: bacteria with 50% concentration + finely chopped rice straw. The parameters observed were C-organic, nitrogen, C/N ratio, phosphorus, potassium, pH, temperature, color, and odor. The results showed that the treatment of the level of chopped organic matter with the concentration of cellulolytic bacteria had no significant effect on the observed variables (C-organic, nitrogen, C/N ratio, phosphorus, potassium, pH, temperature, color, and odor). There is a trend in the treatment of fine rice straw shredding rate + 50% concentration of cellulolytic bacteria that produces good compost quality. The treatment has C-organic content: 34.52%, nitrogen: 1.82%, C/N ratio: 19.10, phosphorus: 0.41%, potassium: 4.65%. Keywords: rice straw, maturity rice, completely randomized design